The cyberdivisions produced by the design of VGI under the platform economy: the case of the restaurant sector in TripAdvisor - Ferreira, Daniela (2021)
There is increasing concern regarding the inequalities produced by digital platforms based on volunteered geographic information (VGI). Several forms of inequalities have been observed, namely the unequal spatial coverage and the uneven levels of usage even in territories with good coverage. However, VGI platforms under the logic of platform economy have generated other forms of spatial inequality that require more attention. The cyberspace within VGI platforms is producing different cyberspatialities, especially with the platformisation processes that have made this type of inequality more evident. With this in mind, this paper aims to explore the making of cyberdivisions under the platform economy. We argue that the design of VGI within digital platforms is generating cyberdivisions in the urban economy. This research is particularly interested in exploring the restaurant sector in the TripAdvisor platform in the city of Lisbon. In this paper, we draw on a representative survey by questionnaire to restaurant firm owners. We obtained 385 responses out of a universe of 3453 restaurants. This sample provides a confidence level of 95% and a confidence interval of 5%. In addition, we webscraped data from TripAdvisor to assess its coverage in Lisbon. This study reveals that there are different forms of online presence and engagement which have generated cyberdivisions.